PENGEMBANGAN LKS IPA BIOLOGI KELAS VIII SMP BERORIENTASI PADA PENDEKATAN KETERAMPILAN PROSES SAINS - Fitri Arsih (Ta'dib, 2010)
At present, it is suspected that students study biology as product and memorize related concepts, theories and laws. Conversely, biology as content or product, process or methods, attitude and technology are rarely applied that makes the subject not as a whole piece and less interesting. Such phenomena challenges the teacher to be more creative and innovative in developing practical learning supports which are simple and easy to be used by both students and teachers. This research aimed at developing worksheets (LKS) for biology subject intended for grade 8 of junior high school students under the topic of photosynthesis employing valid, practical and effective science process skill approach. This study belonged to research and development one. Learning support is developed by means of Four-D (Define, Design, Develop and Disseminate). ‘Disseminate’ is not done. Data collections were conducted by validating and trying out of the learning support. Validations were conducted by six experienced and qualified validators while try out was conducted by applying it to the grade 8 students of SMP Dedikasi Edukasi Kualiva (DEK) Padang to figure out practicality and effectiveness. The study showed that the worksheet using environment-based science process skill approach was in very valid category. Students’ responses toward the worksheet showed positive result with an average response was ≥ 80%. It can be concluded that the worksheet was valid, practical and easy to use.Kata kunci: LKS, keterampilan proses sains